Prescribing indicators for UK general practice: Delphi consultation study. Issue 7258 (12th August 2000) - Campbell, Stephen M; Cantrill, Judy A; Roberts, Dave
Abstract: Objectives: To identify prescribing indicators based on prescribing analysis and cost (PACT) data that have face validity for measuring quality or cost minimisation. Design: Modified two round Delphi questionnaire requiring quantitative and qualitative answers. Setting: Health authorities in England. Participants: All health authority medical and pharmaceutical advisers in the first round and lead prescribing advisers for each health authority in the second round. Main outcome measures: Face validity (median rating of 7–9 on a nine point scale without disagreement) and reliability (rating 8 or 9) of indicators for assessing quality and cost minimisation. Results: Completed second round questionnaires were received from 79 respondents out of 99. The median rating was 7 for cost minimisation and 6 for quality, and in all except four cases individual respondents rated indicators significantly higher for cost than for quality. Of the 41 indicators tested, only seven were rated valid and reliable for cost minimisation and five for quality. Conclusion: The 12 indicators rated as valid by leading prescribing advisers had a narrow focus and would allow only a limited examination of prescribing at a general practice, primary care group, or health authority level.